Kebijakan dan Etika Berteknologi untuk Mengatasi Pelanggaran Hak Cipta di Era Digital - Hidapenta, Detania; Febriyanti, Natasya; Permatasari, Nikie Ailsa; Herlambang, Yusuf Tri (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The digital era has brought drastic changes in the way humans interact with technology, especially in the context of copyright. Technological developments have enabled faster and easier access to digital content, but have also led to an increase in copyright infringement. This article aims to conduct a review of literature studies on policies and ethics that can help overcome copyright violations in the digital era. This research uses a literature study method by collecting references from accredited published articles, both nationally and internationally. Then the references are compiled and analyzed for further conclusions to be drawn. This research provides a deeper understanding of the complexity of copyright issues in the digital era and concludes that to overcome copyright infringement, a combination of policies that are compatible with technological developments, strong ethics and careful digital protection technology is needed.